A disciplina Modelagem na educação matemática na UFMG: percepções junto a estudantes e egressos do curso de licenciatura em Matemática - Danielle Alves Martins (2017)
This research is focused in the initial formation of teachers and the modeling according to the mathematics education. My concerns regarding to my initial formation at UFMG and the experiences that I had with modeling, in this context, were the starting point for the creationof it. In this sense, the general purpose of the research was to identify the perceptions of students and graduates of the course of Mathematic in UFMG's regarding to modeling from the modeling discipline in mathematics education, offered in the second half of 2013 and 2014. It is worth mentioning that, in this context, the discipline is not part of the disciplines that are offered regularly in the course, and its offer has emerged from a gap. To achieve what I was aiming for, I supported myself in the ideas of Polettini, in which the perceptions are the fruits of the reflections on the experiences experienced by each individual. Theseunderstandings directly influenced the methodological construction of the research. Then, I conducted a qualitative survey, where the instruments of collecting data used were documents, questionnaires and interviews. The documents were either important for the description of the research context, and to show how possible the presence of the discipline modeling in mathematics education in the course of mathematics at UFMG. From the questionnaire it was possible to obtain the personal information of the students And information that served as the basis for the preparation of interview questions. The interviews allowed the participants to relate their experiences and reflect on them more naturally. The analysis of the data was constructed primarily from excerpts from the interviews of four participants of the survey: Bruna, Maria, Rogério and Cauã. Considering the speeches of the students it was possible to identify issues related to the formation environment in modeling, modeling from a social and critical approach, and modeling as a proposal for, current and future, pedagogical practice. The modeling seems to have influenced the perceptions of students in regarding to mathematics education, and their perceptions in relation to mathematics in society, in a more general way. Which puts us to reflect again on the potential of disciplines on modeling in the initial formation of mathematics teachers, and in which molds these disciplines are still offered in higher education institutions, especially in the course of formation of mathematics teachers at UFMG.